Sport and dance interventions for healthy young people (15–24 years) to promote subjective well-being: a systematic review. Issue 7 (15th July 2018) - Mansfield, Louise; Kay, Tess; Meads, Catherine; Grigsby-Duffy, Lily; Lane, Jack; John, Alistair; Daykin, Norma; Dolan, Paul; Testoni, Stefano; Julier, Guy; Payne, Annette; Tomlinson, Alan; et al.
Abstract : Objective: To review and assess effectiveness of sport and dance participation on subjective well-being outcomes among healthy young people aged 15–24 years. Design: Systematic review. Methods: We searched for studies published in any language between January 2006 and September 2016 on PsychINFO, Ovid MEDLINE, Eric, Web of Science (Arts and Humanities Citation Index, Social Science and Science Citation Index), Scopus, PILOTS, CINAHL, SPORTDiscus and International Index to Performing Arts. Additionally, we searched for unpublished (grey) literature via an online call for evidence, expert contribution, searches of key organisation websites and the British Library EThOS database, and a keyword Google search. Published studies of sport or dance interventions for healthy young people aged 15–24 years where subjective well-being was measured were included. Studies were excluded if participants were paid professionals or elite athletes, or if the intervention was clinical sport/dance therapy. Two researchers extracted data and assessed strength and quality of evidence using criteria in the What Works Centre for Wellbeing methods guide and GRADE, and using standardised reporting forms. Due to clinical heterogeneity between studies, meta-analysis was not appropriate. Grey literature in the form of final evaluation reports on empirical data relating to sport or dance interventions were included. Results: Eleven out of 6587 articles were included (7 randomised controlled trials and 1 cohort study, and 3 unpublished grey evaluation reports). Published literature suggests meditative physical activity (yoga and Baduanjin Qigong) and group-based or peer-supported sport and dance has some potential to improve subjective well-being. Grey literature suggests sport and dance improve subjective well-being but identify negative feelings of competency and capability. The amount and quality of published evidence on sport and dance interventions to enhance subjective well-being is low. Conclusions: Meditative activities, group and peer-supported sport and dance may promote subjective well-being enhancement in youth. Evidence is limited. Better designed studies are needed. Trial registration number: CRD42016048745; Results.